Further Lunar Occultations from the 2.4m Thai National Telescope - A. Richichi (2018)
© 2017. The American Astronomical Society. All rights reserved.. We present the latest lunar occultation (LO) results obtained at the 2.4 m Thai National Telescope, continuing a program started in 2014. We report on 21 LO events for 20 stellar sources, yielding 7 binary stars, 1 angular diameter, and 1 star with extended circumstellar emission. These results, some of which are obtained for the first time, are discussed in the context of previous observations when available.